Fatigue assessment of post weld geometric treated welded joints: A strain energy density-based approach and test data interpretation - Fuhao Lu; Jinfeng Zhao; Shangchao Zhao; Xiangwei Li; Shizhu Xing (Results in Engineering)
Post-welded geometric treatment (PWGT) can effectively mitigate or eliminate weld defects and improve the fatigue performance of weldments. However, quantitatively evaluating the fatigue improvement resulting from PWGT is still a challenge in engineering practice. In this study, finite element-based averaged elastic strain energy (SED) evaluation approaches for both 2D and 3D joints are proposed and validated in advance. The impact of PWGT on fatigue behaviors is investigated utilizing the SED method. More than 300 fatigue data with detailed information provided in the literature, such as joint types, shapes of geometric treatments, and base materials, were collected and analyzed. It turns out that SED, as an effective parameter, is capable of quantitatively characterizing fatigue improvements from PWGT compared to as-welded conditions. The analysis results indicate that the strength of the base material has a significant impact on the fatigue improvement from PWGT. Then, fatigue design curves are proposed corresponding to the strength of base materials and validated by a set of fatigue data of gusset joints.